Development of a Problem Based Learning Model Assisted by Wordwall to Improve Creative Thinking Skills - Intan Sri Mutiaz Alfi Farhani; Agus Hasbi Noor; Heris Hendriana (Journal of Education and Teaching Learning, 2026)
This study aimed to develop a Problem Based Learning model assisted by the Wordwall application to improve the creative thinking skills of Paket C students in creative economy learning at PKBM Mi’raajul Ummah. This study employed a Research and Development method using the ADDIE model, which consisted of analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 15 eleventh-grade Paket C students. Data collection techniques included observation, interviews, questionnaires, documentation, and creative thinking tests. The results showed that the developed learning model was feasible for implementation based on material expert validation with a percentage of 81.25% and media expert validation with a percentage of 83.3%. The implementation of the learning model was also able to improve students’ creative thinking skills, as indicated by the increase in the average pretest score from 7.9 to 12.2 in the posttest, with an N-Gain value of 0.55 in the moderate category. In addition, the questionnaire results showed a student response percentage of 91.1% in the very good category. Therefore, the Problem Based Learning model assisted by Wordwall was able to create more interactive and contextual creative economy learning and support the development of the creative thinking skills of Paket C students.